RELATIONSHIP MANAGEMENT BETWEEN ELEMENTARY SCHOOL AND COMMUNITY: A POAC APPROACH TO DEVELOPING EDUCATIONAL COLLABORATION - Muhammad Nurrahman; Sri Marmoah (Journal of Elementary Education, 2025)
The relationship between schools and communities is a critical factor in supporting the creation of an inclusive and sustainable educational ecosystem, particularly in the implementation of the Merdeka Curriculum. This article aims to examine school-community relationship management using the POAC (Planning, Organizing, Actuating, Controlling) management approach in a primary education context. This study employed a descriptive qualitative method with data collected through in-depth interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The results show that planning was conducted participatively through deliberative forums and SWOT analysis involving the community; organizing involved parents’ associations and external stakeholders; program implementation included direct community participation in activities such as Market Day, Outing Class, Ramadhan Talkshow, and Jesa School Care; and supervision was carried out through regular evaluations and the use of communication technology as a transparency tool. This strategy fostered tangible collaboration, enhanced the community’s sense of ownership of the school, and established a professional and adaptive relationship. It is concluded that the POAC-based management approach is effective in managing school-community partnerships to improve the overall quality of education.